Pelatihan Perilaku Respek Dan Empati Melalui Metode Role Play Untuk Mencegah Bullying Di SMKN 3 Banjarmasin - Wardah, Ani; Auliah, Nurul; Aminah, Aminah; Andriana, Riya; Pebrianti, Novi (LPPI UMN AL WASHLIYAH, 2024)
Bullying behavior is behavior that is carried out repeatedly by a group of students who have power over weak students with the aim of causing displeasure or pain by other people, either one or several people directly against someone who is unable to fight back. The aim of this community service is to prevent bullying at SMKN 3 Banjarmasin. The participants in this activity were 36 students from class XI b TJKT. The method used is training in respectful and empathetic behavior through the role play method to prevent bullying. As for the activities: Meeting I, namely 1. Orientation and Pre-test, then delivery of role play training rules, and division into groups and roles, 2. Students act out bullying scenes in forms of verbal, physical and cyberbullying. 3. Students act in the positions of victims, perpetrators and witnesses of bullying. Meeting II, namely (4) Students act out a bullying prevention scene by being respectful, empathetic and helping the victim. 5. Students act out a reconciliation scene between the victim and the perpetrator of bullying, (7) Discussion after the role play to summarize the learning and feelings experienced. Next, evaluate the progress of training results. The training results showed that there was a significant difference between the pretest and posttest scores for SMKN 3 Banjarmasin students, with an increase in scores of 45 points after participating in the role play training. This increase indicates that role play-based training methods are effective in increasing students' respectful and empathetic behavior.